The role of microRNAs in B-cell development and function - Li, Jingyi; Wan, Ying; Ji, Qing; Fang, Yongfei; Wu, Yuzhang (Cellular & molecular immunology, 2013)
MicroRNA （miRNA）-mediated gene silencing at the translational level has led to novel discoveries for numerous biological processes. Recently, there has been increasing evidence to indicate that miRNAs are involved in normal immune functions and inflammation. In this review, we focus on recent advances that have elucidated the role of miRNAs in B-cell development, differentiation, apoptosis and function. While the regulatory mechanisms of miRNAs in controlling and maintaining B-cell fate remain largely uncharacterized, further studies on miRNAs and their targets will increase our understanding of B-cell development and function. Such studies may be able to provide new therapeutic strategies for treating autoimmune diseases.